Analytics at work : smarter decisions, better results - Davenport, Thomas H., 1954-; Harris, Jeanne G.; Morison, Robert (Boston, Mass. : Harvard Business Press, 2010)
"In their previous book, Competing on Analytics, Thomas H. Davenport and Jeanne G. Harris showed how pioneering firms were building their entire strategies around their analytical capabilities. Rather than "going with their gut" when pricing products, maintaining inventory, or hiring talent, managers in these firms use data, analysis, and systematic reasoning to make decisions that improve efficiency, risk management, and profits." "Now, in Analytics at Work, Davenport, Harris, and coauthor Robert Morison reveal how all managers can effectively deploy analytics in their day-to-day operations - one business decision at a time. The authors show how many types of analytical tools, from statistical analysis to qualitative measures like systematic behavior coding, can improve decisions about everything from what new product offering might interest customers to whether marketing dollars are being most effectively deployed." "Based on new research and illustrated with examples from companies including Humana, Best Buy, Progressive Insurance, and Hotels.com, this implementation-focused guide outlines a five-step model for deploying and succeeding with analytical initiatives."--BOOK JACKET.
What it means to put analytics to work -- Data : the prerequisite for everything analytical -- Enterprise : integrating across organizational silos -- Leadership : the deciding DELTA factor -- Targets : picking your spots for analytics -- Analysts : managing scarce and valuable talent -- Embed analytics in business processes -- Build an analytical culture -- Review your business comprehensively -- Meeting challenges along the way -- Toward more analytical decisions and better results.
Includes bibliographical references (pages 189-195) and index.
Description based on print version record.
Keywords: Business intelligence; Decision making; Business intelligence; Decision making; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books